2012
DOI: 10.1016/j.neuroimage.2011.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Activation patterns during action observation are modulated by context in mirror system areas

Abstract: The role of the mirror system in action understanding has been widely debated. Some authors have suggested that the mirror system plays an important role in action understanding (Rizzolatti and Sinigaglia, 2010), whereas others have claimed that direct evidence to support this view is lacking (Hickok, 2009). If mirror neurons have an active role in action understanding rather than passive visuomotor transformation during action observation, they should respond differently to the observation of actions dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 58 publications
2
39
0
1
Order By: Relevance
“…Similarly, activity in the motor cortex during action observation depends on attention to those actions (Schuch et al, 2010). Moreover, participantsʼ intentions, for example, to understand an action or to identify physical features, are associated with specific patterns of cortical activation during action observation (Molenberghs, Hayward, Mattingley, & Cunnington, 2011). This study extends these findings by showing that top-down regulation changes not only the strength of interactions between the visual system and the motor system but also their direction.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, activity in the motor cortex during action observation depends on attention to those actions (Schuch et al, 2010). Moreover, participantsʼ intentions, for example, to understand an action or to identify physical features, are associated with specific patterns of cortical activation during action observation (Molenberghs, Hayward, Mattingley, & Cunnington, 2011). This study extends these findings by showing that top-down regulation changes not only the strength of interactions between the visual system and the motor system but also their direction.…”
Section: Discussionsupporting
confidence: 65%
“…non-identical but goal-related actions) are facilitated during action observation is determined in a dynamic, context-dependent fashion [30]. Participants’ intentions, either to understand an action or to identify physical features, is associated with distinct patterns of cortical activation during action observation [31]. Interestingly, cognitive context appears to change the strength and direction of visuomotor interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported activation in the inferior parietal areas during action observation 23,37 and some data indicate that the parietal cortex is associated with observation of goal-oriented movement more than observation of intransitive movement. For instance, Lorey and colleagues (2013) tested presentation of different conditions of action observation using fMRI.…”
Section: Discussionmentioning
confidence: 99%